A comparative analysis between Mexican and Chinese health systems - Garcia Tapia, Gabino; Esparza Rodriguez, Saul Alfonso (Horizonte Sanitario, 2023)
Objective: The comparative network analysis of national health macrosystems is an area whose academic development has not reached due relevance if its influence on decision-making related to the design of public health policies is considered; the establishment of comparative elements between two socially, economically and culturally distant countries, such as Mexico and China, is a complex process given the difficulty of locating equivalent evaluation indicators among some of its elements. Materials and methods: The present work reflects on the similarities and dissimilarities between the national health systems, with an impact on the care provided to the most vulnerable population segments, applying a comparative nodes and networks analysis considering social and economic factors. Results: The network analysis shows that, for practical purposes, the nodes considered in the Mexican health system is superior to those nodes identified in the Chinese health system in terms of quality, mainly in nodes such as convenience of the location, using cutting-edge technology in health institutions and the skill and competence of medical personnel; conversely, the Chinese system is superior to the Mexican in terms of efficiency, mainly involuntary co-payment insurance systems to reduce the catastrophic health expenditure of the vulnerable rural population. Conclusions: The conclusions drawn may serve for subsequent studies to identify opportunities for improvement, correlations and/or trends that could be implemented in the Mexican health system, once the pertinent feasibility studies have been carried out. Keywords: Health Management; Population Health Management; Comparative studies; Mexico; China.